2020
DOI: 10.1101/2020.03.10.985895
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell RNA-seq analysis reveals compartment-specific heterogeneity and plasticity of microglia

Abstract: Microglia are heterogeneous and ubiquitous CNS-resident macrophages that maintain homeostasis of neural tissues and protect them from pathogen attacks. Yet, their differentiation in different compartments remains elusive. We performed single cell RNA-seq (scRNA-seq) analysis to compare the transcriptomes of 32760 microglia in adult mouse (C57/Bl) brains and spinal cords to identify microglial subtypes in these CNS compartments. Cortical microglia from 2-month mice consisted of a predominant population of the h… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 41 publications
3
10
0
Order By: Relevance
“…These imply that cluster #13 represents dividing microglia. These are consistent with reports showing the complex heterogeneity in microglia populations especially during early development, compared with adult stages 54,55 . The smallest cluster of cells (#14, n=125 cells) is distinguished as oligodendrocyte precursor cells owing to expression of PTPRZ1, PMP2 and PDGFRA (Fig.…”
Section: Resultssupporting
confidence: 93%
“…These imply that cluster #13 represents dividing microglia. These are consistent with reports showing the complex heterogeneity in microglia populations especially during early development, compared with adult stages 54,55 . The smallest cluster of cells (#14, n=125 cells) is distinguished as oligodendrocyte precursor cells owing to expression of PTPRZ1, PMP2 and PDGFRA (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Microglial homeostatic genes (e.g., Tmem119 and Siglech) were down‐regulated, whereas pro‐inflammatory genes (e.g., Ccl2 and Nfkbia) were up‐regulated at the single‐cell level (Sousa et al, 2018). Similarly, using single‐cell RNA sequencing, a distinct microglial population (using C57/Bl and HIV gp120 transgenic mouse models) in the cortex and the spinal cord was found (Zheng et al, 2021). Notably, these microglia showed differential signatures based on the expression of genes involved in homeostasis (e.g., Cx3cr1 and Tmem119), regulation of immune responses (e.g., Il1a and Ccl4), and cytokine and chemokine genes (e.g., Il1b and Ccl2; Zheng et al, 2021).…”
Section: Microglial Activation Following Cuprizone (Cpz)‐feedingmentioning
confidence: 96%
“…Similarly, using single‐cell RNA sequencing, a distinct microglial population (using C57/Bl and HIV gp120 transgenic mouse models) in the cortex and the spinal cord was found (Zheng et al, 2021). Notably, these microglia showed differential signatures based on the expression of genes involved in homeostasis (e.g., Cx3cr1 and Tmem119), regulation of immune responses (e.g., Il1a and Ccl4), and cytokine and chemokine genes (e.g., Il1b and Ccl2; Zheng et al, 2021). Another recent study by Hammond et al (2019) revealed at least nine transcriptionally distinct microglial populations (in C57Bl/6J mice) that express unique sets of genes.…”
Section: Microglial Activation Following Cuprizone (Cpz)‐feedingmentioning
confidence: 96%
“…It is not yet known whether this subclass has a distinctive response to systemic pro-inflammatory stimuli, but distinctive responses appear to occur during localized CNS inflammation. In mice, single cell RNA-seq shows upregulation of a interferon-response gene signature in a subpopulation of microglia after demyelinating brain injury (190,191). In patients with multiple sclerosis, single nucleus RNAseq reveals marked expansion of microglia, with transcriptional changes toward a phagocytosing phenotype (192).…”
Section: Microgliamentioning
confidence: 99%